Gene expression signatures of human primary monocytes from healthy individuals and XLA patients using deep RNA sequencing analysis / Hoda Mirsafian - Hoda, Mirsafian (2017)
Monocytes are essential cells of the innate immune system. They play important roles in the initiation and declaration of inflammation, generally through release of inflammatory cytokines, ROS (Reactive Oxygen Species) during phagocytosis and the activation of adaptive immune system. In this thesis, the transcriptome of primary monocytes from 6 healthy subjects and 3 patients with X-linked agammaglobulinemia (XLA), one of the inherited form of Primary immunodeficiency diseases (PIDs), were sequenced using deep polyadenylated (Poly(A)+) paired-end RNA sequencing (RNA-Seq) technique. The gene expression profiling was conducted on both healthy and disease RNA-Seq datasets. Approximately 1.3 billion reads were generated from healthy subject’s RNA-Seq datasets. Using this datasets, the expression of 17,657 genes (including 11,644 protein-coding, 3,515 non-coding, and 2,498 pseudogenes) and 81,419 transcripts (including 70,457 annotated transcripts and 4,935 novel transcripts) were profiled from healthy subjects. The sequencing also generated approximately 477 million reads from XLA patients’ samples which lead to the profile of 17,510 genes (including 11,788 protein-coding, genes 3,681 non-coding genes, and 2,041 pseudogenes) and 62,367 transcripts (including 58,136 annotated and 4,231 novel transcripts). A comparative study was conducted on gene expression profiles of 3 healthy male and 3 healthy female subjects to look into possible gender differences in expression patterns of immune-related genes. The results revealed that the innate immune-related genes are not equally expressed in primary monocytes of healthy male and female which indicated the disparity in innate immune response based on gender. Furthermore, the RNA-Seq datasets of the 6 healthy subjects were integrated with public domain RNA-Seq datasets of human monocytes to construct the gene reference catalogue of primary monocytes from healthy state monocytes. The long non-coding RNAs (lncRNAs) expression patterns analysis in monocytes was also conducted using these datasets which led to identification of several novel long intergenic non-coding RNAs (lincRNAs) that have not been previously reported in monocytes. A comparative study was performed on gene expression profiles of XLA patients and healthy male subjects. The analysis detected several innate immune-related genes which are differentially expressed between XLA patients and healthy subjects, suggesting impaired immune function of monocytes and increased of susceptibility to apoptosis in monocytes of XLA patients. The results also showed the significant changes in lncRNAs expression patterns in primary monocytes of XLA patients compared to healthy subjects which may play roles in regulating the cell cycle and apoptosis in primary monocytes of XLA patients. The high-resolution genome-wide transcriptome expression profile of primary monocytes present in this study would provide a better understanding of monocytes characterization and function in healthy and XLA states. It also facilitates the detailed analyses of innate immune system abnormalities and novel pathomechanism concerning XLA.